2019
DOI: 10.3390/ma12193167
|View full text |Cite
|
Sign up to set email alerts
|

Co-Immobilization of Glucose Dehydrogenase and Xylose Dehydrogenase as a New Approach for Simultaneous Production of Gluconic and Xylonic Acid

Abstract: The conversion of biomass components catalyzed via immobilized enzymes is a promising way of obtaining valuable compounds with high efficiency under mild conditions. However, simultaneous transformation of glucose and xylose into gluconic acid and xylonic acid, respectively, is an overlooked research area. Therefore, in this work we have undertaken a study focused on the co-immobilization of glucose dehydrogenase (GDH, EC 1.1.1.118) and xylose dehydrogenase (XDH, EC 1.1.1.175) using mesoporous Santa Barbara Am… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 40 publications
0
6
0
1
Order By: Relevance
“…The enzyme contents were estimated based on the enzymatic activity as described in Supplementary Materials, Section SI5 and Figure S4 . This approach followed previous reports where the number of active immobilized molecules has been estimated by quantifying their catalytic activity towards a substrate with the aid of colorimetric or fluorescent methods [ 69 , 74 , 75 , 76 ]. Figure 3 c shows the immobilization yield obtained according to content of Laccase.…”
Section: Resultsmentioning
confidence: 99%
“…The enzyme contents were estimated based on the enzymatic activity as described in Supplementary Materials, Section SI5 and Figure S4 . This approach followed previous reports where the number of active immobilized molecules has been estimated by quantifying their catalytic activity towards a substrate with the aid of colorimetric or fluorescent methods [ 69 , 74 , 75 , 76 ]. Figure 3 c shows the immobilization yield obtained according to content of Laccase.…”
Section: Resultsmentioning
confidence: 99%
“…Bachosz et al co-immobilized xylose dehydrogenase and alcohol dehydrogenase onto silica core–shell for xylose conversion to xylonic acid and cofactor regeneration . Similarly, glucose dehydrogenase and xylose dehydrogenase were immobilized onto mesoporous amorphous silica for coproduction of gluconic acid and xylonic acid . Zdarta et al demonstrated enzymatic production of xylonic acid and gluconic acid from biomass-derived xylose and glucose via immobilization of xylose dehydrogenase and glucose dehydrogenase onto porous silica nanoparticles .…”
Section: Discussionmentioning
confidence: 99%
“…26 In contrast, the two enzymes were xed in the same carrier bead in the dual-enzyme co-immobilization system would reduce the transport time of the substrate and intermediate loss due to diffusion, 52 the substrate was instantly converted to the nal product due to that two closely enzymes constituted a efficiently cascade biocatalyst. 28,[53][54][55] Therefore, this co-immobilization system enabled a fast transfer of substrate, thus enhancing the overall catalytic efficiency of the cascade reactions.…”
Section: Effect Of Temperature and Ph On Activity And Reusability Of mentioning
confidence: 99%